Metagenomic analysis of human, animal, and environmental samples identifies potential emerging pathogens, profiles antibiotic resistance genes, and reveals horizontal gene transfer dynamics - Rajindra Napit; Anupama Gurung; Ajit Poudel; Ashok Chaudhary; Prajwol Manandhar; Ajay Narayan Sharma; Samita Raut; Saman Man Pradhan; Jyotsna Joshi; Mathilde Poyet; Mathieu Groussin; Rajesh M. Rajbhandari; et al. (Scientific Reports)
Abstract Antimicrobial resistance (AMR) poses a significant threat to global health. The indiscriminate use of antibiotics has accelerated the emergence and spread of drug-resistant bacteria, compromising our ability to treat infectious diseases. A One Health approach is essential to address this urgent issue, recognizing the interconnectedness of human, animal, and environmental health. This study investigated the prevalence and transmission of AMR in a temporary settlement in Kathmandu, Nepal. By employing shotgun metagenomics, we analyzed a diverse range of samples, including human fecal samples, avian fecal samples, and environmental samples. Our analysis revealed a complex interplay of pathogenic bacteria, virulence factors (VF), and antimicrobial resistance genes (ARGs) across these different domains. We identified a diverse range of bacterial species, including potential pathogens, in both human and animal samples. Notably, Prevotella spp. was the dominant gut bacterium in human samples. Additionally, we detected a wide range of phages and viruses, including Stx-2 converting phages, which can contribute to the virulence of Shiga toxin-producing E. coli (STEC) strains. Our analysis revealed the presence of 72 virulence factor genes and 53 ARG subtypes across the studied samples. Poultry samples exhibited the highest number of ARG subtypes, suggesting that the intensive use of antibiotics in poultry production may contribute to the dissemination of AMR. Furthermore, we observed frequent horizontal gene transfer (HGT) events, with gut microbiomes serving as key reservoirs for ARGs. This study underscores the critical role of a One Health approach in addressing AMR. By integrating human, animal, and environmental health perspectives, we can better understand the complex dynamics of AMR and develop effective strategies for prevention and control. Our findings highlight the urgent need for robust surveillance systems, judicious antibiotic use, and improved hygiene practices to mitigate the impact of AMR on public health.